Do Mandalas Exhibit Archetypal Patterns Based on Kellogg’s MARI? A Pilot Study - van der Vennet, Renée; Cassella, Caitlin (Canadian Journal of Counselling and Psychotherapy, 2020)
The Mandala Assessment Research Instrument (MARI) can be used to assess mandalas drawn by participants as part of the therapeutic process. This study investigated whether a set of 85 mandalas drawn over 15 years by the first author depicts archetypal patterns as defined by Kellogg’s Great Round of archetypal stages in mandalas in the MARI and if these patterns relate to significant events in the person’s life. The research questions are: (a) “Do archetypal patterns and MARI stages, as depicted in the MARI Great Round, appear in this dataset?” (b) “Do archetypal patterns correspond to significant events in the first author’s life?” and (c) “Do certain archetypal patterns relate to certain significant events?” The results demonstrated that archetypal patterns exist in mandalas. With the appropriate training, counsellors could use mandalas and the MARI throughout the therapeutic process.